A significant pure population of the dark European honey bee (Apis mellifera mellifera) remains in Ireland. Issue 3 (27th May 2018) - Hassett, Jack; Browne, Keith A; McCormack, Grace P; Moore, Elizabeth; Society, Native Irish Honey Bee; Soland, Gabrielle; Geary, Michael
Abstract : The natural range of the dark European honey bee, Apis mellifera mellifera has been significantly reduced in recent years as a result of importation and replacement of queens with those of other Apis subspecies. Previous studies have indicated that a substantial amount of A. m. mellifera populations throughout Europe are heavily hybridized but that pockets of pure populations do still exist and need to be protected as this subspecies is a highly valuable gene pool and is of considerable conservational interest. Small numbers of Irish bees have been included in previous studies, but scientific information is limited and questions remain about the genetic diversity of bees in Ireland and the extent of introgression into apparent black bees from introduced races and hybrids. The objective of this study was to investigate the genetic composition of the A. m. mellifera population on the island of Ireland with both nuclear (microsatellites) and mitochondrial markers. Molecular data was generated from 412 bees sampled from 24 counties across the island. Mitochondrial data identified 34 different haplotypes, with 63% of bees having sequences identical to three European haplotypes but all other haplotypes being novel. Population structure analysis using microsatellite markers indicates that the Irish population is genetically diverse and that 97.8% of sampled bees were determined to be pure A. m. mellifera . Results from cluster analysis using a Bayesian model approach, and the presence of novel alleles, shows evidence of distinctiveness within the Irish population.